CULTURAL MEMORY AND IDENTITY IN POSTCOLONIAL SOCIETIES (Eureka Journal of Humanities and Social Research, 2025)
This paper examines how cultural memory functions as a tool for reconstructing national and individual identities in postcolonial societies. Drawing from examples in South Asia, Africa, and the Caribbean, it explores how memory—through literature, oral history, and visual art—serves as resistance to colonial narratives. Using postcolonial theory and cultural semiotics, the paper argues that reinterpreting memory allows marginalized communities to reclaim identity and agency in global discourse.
Keywords: Postcolonialism, cultural memory, identity, decolonization, heritage